Emerging Non-Thermal Food Processing Technologies (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
There is a strong consumer trend towards high-quality and healthy foods with ‘fresh‐like’ characteristics. On the other hand, thermal processing technologies, especially conventional ones, negatively affect both the sensory and nutritional properties of foods. At the same time, limited shelf-life and safety concerns of fresh foods necessitate food processing. Therefore, scientists are exploring the possibility of using nonthermal technologies for various purposes such as shelf-life extension and safety improvement. However, their applicability and scalability are still under intensive investigation. This reprint presents examples of studies in non-thermal emerging food processing technologies. It provides practical examples that can help graduate students further understand the concepts involved in emerging non-thermal technologies; therefore, it can be used as a teaching material/reference in universities. Moreover, the benefits of these novel technologies highlighted in this reprint could be utilized by the food industry’s R&D to enhance academic-industry collaborations and possible commercialization.